Environmental and biosecurity-related risk factors for African swine fever outbreaks in peninsular Malaysia - Ramachanderen, Pravina Vathi; Ramanoon, Siti Zubaidah; Mohd Nor, Norhariani (Istanbul University, 2024)
As African swine fever is a serious threat to the pig industry in Malaysia, scientifically analyzed information on the disease is vital for better control of the disease. The present study was conducted to determine the environmental and biosecurity-related risk factors for African swine fever outbreaks among domestic pig farms in Peninsular Malaysia. Data collected through a face-to-face interview with the pig farmers using a structured, close-ended questionnaire were analyzed using univariate and multivariate logistic regression. The final logistic regression model identified (1) presence of wild birds in the pig pens area (OR = 0.08; 95 CI, 0.01–0.74; p = .03), (2) presence of attractive crops/fruit trees surrounding the farm (OR = 4.00; 95 CI = 1.25–12.82; p = 0.02), (3) sharing of workers with other farms (OR = 6.11, 95 CI, 1.46–25.61; p = .01), (4) entry of visitor’s vehicle into farm (OR=0.14; 95 CI, 0.02–1.00; p=.05), (5) entry of feed truck into farm (OR=5.45; 95 CI, 1.03–28.92; p=.04), (6) presence of biting insects such as flies, mosquitoes on pig’s body which irritates the pigs (OR=0.21; 95 CI, 0.06–0.80; p=.02), and (7) farm prone to rodent access and infestation (OR=0.15; 95 CI, 0.03–0.79; p=.03) as the significant risk factors for African swine fever outbreaks in the studied farms. These findings highlight the need to strengthen on-farm biosecurity practices, farm management practices, and strict control of vehicle movement into the farm to prevent African swine fear outbreaks in the future. © 2024 Istanbul University. All rights reserved.